Analisis Faktor-Faktor Yang Dapat Meningkatkan Kepercayaan Konsumen Terhadap Risiko Belanja Online Pada Lazada - Candra Emelia Fransisca; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Lazada is a pioneer of e-commerce (online shopping) in some of the fastest growing countries in the world offering a fast, secure and convenient online shopping experience. This study was conducted to determine factors that can increase consumer confidence in the risks that occur when doing online shopping on Lazada. The model design used is a modification of previous studies focusing on perceived risk to increase consumer trust. Techniques used to perform data collection is a questionnaire with the number of respondents as much as 292. To perform data analysis used Path Analysis. The reason for the use of Path Analysis because to know the causal relationship of model relationship between variables so that can know which path is most appropriate used for independent variable to dependent variable. The results obtained are Social risk variable, and Financial risk individually has a significant influence on Consumer trust variable.